Uterine blod flow during pregnancy - Apaza Valencia, John (2015)
Both systemic and uterine cardiovascular physiological changes in pregnancy are fundamental for blood flow increase in the uterus, microcirculation and circulation in the intervillous space. Pathophysiological changes in uterine and placental circulation are associated to preeclampsia and intrauterine growth restriction. In this review the anatomy of the uterine blood flow, uterine blood flow during pregnancy and clinical implications are described.